Clinical Analysis of Adult Severe Open-Globe Injuries in Central China - Chen, Hongling; Han, Junjun; Zhang, Xianliang; Jin, Xuemin (Frontiers in Medicine, 2021)
Purpose: To describe the characteristics, management, and outcomes of adult severe open-globe injured (OGI) eyes. Methods: Retrospective chart review of inpatients with initial visual acuity of LP or NLP associated with OGI between 2017 and 2020 at Department of Ophthalmology, Henan Eye Institute, Henan Eye Hospital, Henan provincial People’s Hospital. Results: Six hundred twenty-five eyes of 622 adult patients with initial visual acuity of LP or NLP associated with open-globe injuries (OGIs) were included. The mean age was 47.8±14.1 years with the range from 18 to 91 years. Significant male predominance was noted (81.5%). The most common type of these severe OGIs was rupture (65.8%). Traffic accidents accounted for 13.5% followed by fall/tumble (10.9%) and nail/wire (10.9%) of all the severe OGIs. Almost half of the injuries happened at workplace (47.2%). Initially, 78.7% eyes just received primary debridement and wound closure, while 8.5% eyes with no possible of anatomical reconstruction received enucleation. After initial management, 350 eyes received subsequent operation, including 239 eyes underwent vitrectomy + silicone oil/(+ cataract remove). Finally, over 6 months follow-up, 137 eyes (21.9%) were enucleated, 150 eyes (24.0%) got atrophied, while 132 eyes (21.1%) retain some visual acuity. Fifty-three eyes (8.5%) got visual acuity of 0.3-1.5. Conclusion: Severe OGIs are most seen in the young, middle-aged, and male working population and remain a serious public health problem, resulting in significant vision loss or enucleation of eyes. Effective preventive measures should be taken for the individuals in these groups.